القيادة العسكرية والتخطيط الاستراتجي لرسول الله صلى الله عليه وسام في غزوة أحد - 'Aishah 'Abd al-Razaq; عائشة عبد الرزاق (Universiti Sains Islam Malaysia, 2022)
The topic of this research is " The Strategy Rasulullah S.A.W in War of Uhud". This title has been chosen to analyzed and identified what is the strategy had used by Rasulullah S.A.W in that war. It is also to research about the situation in that war. Besides that, women have a main responsible in this war. Therefore to identified the role of women in this war. Based on this research, the researcher take many alternative to find the data to get more information related to this research, such as the library Islamic University College of Malaysia, the library of Islamic Center and other Universities Libraries. Moreover, the author also referred based on Al- Quran and Hadith to get the better of evidence. Nevertheless, this war gave more effort to the Ummah to carry out their responsibility to not selfish and to throw out the felling of greedy in property. Because of this reason, it is became damage to the society.